Global Research Trends of Digital Learning Media in Science Education: A Bibliometric Analysis - Nurullina Fajri; Siti Sriyati; Diana Rochintaniawati (Postgraduate, University of Mataram, 2024)
This research aims to identify global research trends on digital learning media in science education through a bibliometric analysis approach. A total of 915 publications were found in the Scopus database related to keywords. Based on criteria, 100 documents were selected and analyzed from 2018 to 2022. Bibliometric data was processed using VOSviewer version 1.6.17. The results of the analysis show that every year there is a significant increase in digital learning media research in science education. The active author with highest publications is Reyna, J., with 6 articles and 52 citations. Then, VOSviewer mapping revealed several current themes related to digital learning media which are divided into 7 clusters; such as ICT, digital explanation, and representation in clusters in cluster 1; artificial intelligence, mobile learning, internet forums in cluster 2; educational technology, human experimentation, and video recording in cluster 3; online learning, digital learning, and multimedia learning in cluster 4; gamification, social networks and YouTube in cluster 5; augmented reality in cluster 6; digital technology, distance learning, and the internet in cluster 7. The results of this research provide a comprehensive understanding and can be used as a basis for further research.